9/11 : the pretext - Husain, N.M
9/11 was not the end of an event. It was rather a beginning; the beginning of creating a prominent myth in the international politics. If that myth has to exist, several sub-myths have to be created a alongside. FBI and Mossad, the Israeli counterpart of CIA, are of the opinion that at least two years Are needed to carry out an attack of the proportion of 9/11. Why did the British PM's dossier not give a single piece of evidence against the activities of Al Qaeda and Bin Laden? Why did it leave unsaid The putative role of the rightist militia which is responsible for the largest terror attack in the US? Why did the government, rather than presenting a cementing proof, harp on the role of Bin Laden without even giving a hint on the rightists, although the latter deserved more suspicion than the former? The doubt lingered. Major news organisations in the US and UK including AP, AFP, Reuters, CNN, BBC, Fox News and C-Span never explained, or posed for that matter, the doubts on the dossier and other official versions of the 9/11.This book, by freelance investigative journalist NM Hussain, attempts to explore some unsaidmysteries behind 9/11.